Semi-continuous emulsion copolymerization of vinyl acetate and butyl acrylate using a new protective colloid. Part 1. Effect of different emulsifiers - Sarac, Ayfer; Yidirim, Huseyin (WILEY, 2006)
Vinyl acetate and butyl acrylate copolymers were synthesized in the presence of ammonium persulfate initiator, emulsifiers having different character such as non-ionic and anionic+non-ionic emulsifiers, and N-methylol acrylamide as a new protective colloid in a classical glass reactor. The monomer ratio was chosen 85:15. In the case of mixture emulsifiers, the series of non-ionic emulsifiers which have 10 to 40 moles ethoxylated nonyl phenol except 20 moles were combined with sodium dodecyl benzene sulfonate. The effects of the new colloidal stabilization agent, and different emulsifiers on the physicochemical properties of the copolymers were investigated at a constant temperature of 70 degrees C by measuring conversion, viscosity, molecular weights, and molecular weight distribution, respectively, by using gravimetric method, Brookfield viscometer, viscometric method, and gel permeation chromatograpy. It was determined that the original copolymer latexes viscosities increased with the increased chain length for the two types of emulsifiers, in general. Similar changes were also found in viscosity average, number average and weight average molecular weights of the copolymers for the different types of emulsifiers. Copyright (c) 2006 John Wiley & Sons, Ltd.
Keywords: emulsion polymerization; latices; surfactants; stabilization; N-methylol acrylamide; ETHOXYLATION DEGREE; POLYMERIZATION; SURFACE; BATCH; Polymer Science